Plasmid Design for Tunable Two‐Enzyme Co‐Expression Promotes Whole‐Cell Production of Cellobiose. Issue 11 (7th August 2020) - Schwaiger, Katharina N.; Voit, Alena; Dobiašová, Hana; Luley, Christiane; Wiltschi, Birgit; Nidetzky, Bernd
Abstract: Catalyst development for biochemical cascade reactions often follows a "whole‐cell‐approach" in which a single microbial cell is made to express all required enzyme activities. Although attractive in principle, the approach can encounter limitations when efficient overall flux necessitates precise balancing between activities. This study shows an effective integration of major design strategies from synthetic biology to a coherent development of plasmid vectors, enabling tunable two‐enzyme co‐expression in E. coli, for whole‐cell‐production of cellobiose. An efficient transformation of sucrose and glucose into cellobiose by a parallel (countercurrent) cascade of disaccharide phosphorylases requires the enzyme co‐expression to cope with large differences in specific activity of cellobiose phosphorylase (14 U mg −1 ) and sucrose phosphorylase (122 U mg −1 ). Mono‐ and bicistronic co‐expression strategies controlling transcription, transcription‐translation coupling or plasmid replication are analyzed for effect on activity and stable producibility of the whole‐cell‐catalyst. A key role of bom (basis of mobility) for plasmid stability dependent on the ori is reported and the importance of RBS (ribosome binding site) strength is demonstrated. Whole cell catalysts show high specific rates (460 µmol cellobiose min −1 g −1 dry cells) and performance metrics (30 g L −1 ; ∼82% yield; 3.8 g L −1 h −1 overall productivity) promising for cellobiose production. Abstract : Co‐expression for high‐yield production of two enzymes in favorable activity ratios represents a main bottleneck in whole‐cell bioconversions. Here, the authors present design strategies from synthetic biology to fine‐tune activity ratios for whole cell production of cellobiose. Cellobiose is synthesized bottom‐up from sucrose and glucose by the action of two phosphorylases with distinct specific activities.